81.3k views
23 votes
Solve the equation -7(-1+3x)-7x=-133​

User Kelvinji
by
4.7k points

2 Answers

9 votes

Answer:

x = 5

Explanation:

To solve an equation, isolate the variable.

1) Expand the left side of the equation. Distribute the -7 to the terms inside the parentheses.


-7(-1+3x)-7x = -133\\7 -21x-7x = -133

2) Then, combine like terms. Combine -21x and -7x to make a single x-term and subtract both sides by -7.


7-28x=-133\\-28x=-140

3) Then, divide both sides by -28 to find the answer.


-28x = -140\\x = 5

User Kjohri
by
5.2k points
14 votes

Answer:

x = 5

Explanation:

-7(-1 + 3x) - 7x = -133

According to PEMDAS, we want to look at the parentheses first.

In this case, the expression within the parentheses is already fully simplified. There are no exponents, so we will move on to multiplication. Distribute the -7 across the parentheses.

7 - 21x - 7x = -133

Now combine the variables.

-21x - 7x + 7 = -133

-28x + 7 = -133

Now combine the constants.

-28x = -140

isolate x by dividing both sides by -28.

x = 5

Check this by plugging this value back into the original equation.

-7(-1 + 3(5)) - 7(5) = -133

Follow PEMDAS (the underlined values are the components we handled)

-7(-1 + 15) - 7(5) = -133

-7(14) - 7(5) = -133

-98 - 35) = -133

-133 = - 133

Your answer is correct.

Hope this helps!

User Dnickels
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.